The Effect of Digital Transformation on the Effectiveness of Human Resource Management (A Study at Lowokwaru District, Malang City) - Lilinda Osin; Anung Prasetyo Nugroho; Wulan Puji Lestari (International Research & Development for Human Beings (IRDH), 2026)
Digital transformation has not yet been fully implemented optimally in improving the effectiveness of HRM within the sub-district. This study aims to determine the effect of digital transformation on the effectiveness of human resource management (HRM) at the Lowokwaru District Office, Malang City, where digital transformation is measured through indicators of information system utilization, document digitization, work process automation, and leadership support, while HRM effectiveness is measured through work process efficiency, accuracy of employee information, performance assessment, and employee discipline and responsibility. The research method used is quantitative with a descriptive and associative approach, with data collection techniques through questionnaires to 34 respondents of Lowokwaru District employees, and data analysis using validity tests, reliability, classical assumptions, simple linear regression, coefficient of determination (R²), F test, and t test with the help of SPSS. The results of the study indicate that digital transformation has a positive and significant influence on HRM effectiveness, so that increasing the application of digital technology in organizations needs to be continuously carried out to improve employee performance and the quality of public services.